Teaching history in primary schools - Hoodless, Pat, 1947- (Achieving QTS., 2008)
This book introduces trainees and newly qualified teachers to the teaching of history in primary schools, and covers key concepts, skills and knowledge for the history curriculum at Foundation Stage, KS1 and KS2. Contents include planning, teaching and learning strategies, assessment, reflection and evaluation, as well as a range of practical ideas for classroom activities and cross-curricular themes. Each chapter is underpinned by national and international research; also included are links to important themes such as citizenship, out-of-school learning, sustainability, diversity and inclusiv.